A Sulfoxide Reagent for Sulfinylative Cross-Coupling - Saito, Fumito (Synlett, 2023)
I recently documented the strategic use of a sulfoxide reagent as a sulfur monoxide equivalent to enable one-pot, three-component syntheses of sulfoxides and sulfinamides. The sulfoxide reagent donates the SO unit upon the reaction with Grignard reagents (RMgX) as sulfenate anions (RSO–). The anionic sulfur intermediates can be readily transformed into sulfoxides and sulfinamides via trapping with appropriate carbon and nitrogen electrophiles. This Synpacts article highlights my first efforts to establish a general sulfinylative cross-coupling platform.1 Introduction2 Development of a Sulfoxide Reagent as a Sulfur Monoxide Equivalent3 Conclusions and Future Directions
Keywords: sulfinylative cross-coupling; Grignard reagents; one-pot synthesis; sulfinamides; sulfoxides